IMPACT OF MERCURY CHLORIDE EXPOSURE ON SOME OF IMMUNOLOGICAL AND BIOCHEMICAL ASSAYS OF COMMON CARP, CYPRINUS CARPIO - Mustafa, S. A.; Al-Rudainy, A. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This work was designed to evaluate the influence of mercury chloride on some of biochemical and immunological biomarkers in common cap, Cyprinus carpio. Around of 120 fish were randomly allocated into four groups (30 fish per group) in triplicates as follows; first group act as control group provided with water only without adding HgCl2; G1, G2 and G3 were exposed to waterborne HgCl2 at levels of 0.01, 0.05 and 0.1 mg l-1 respectively. After one month exposure to HgCl2, there were significantly decreased (P<0.05) in lymphocyte transformation index and in phagocytic and lysozyme activities. Besides, biochemically, Albumin and globulin content exhibited significantly declined (P<0.05) particularly at higher dose of HgCl2. In contrast, blood glucose value and urea showed significantly increased (P<0.05) especially in G3. On the other hand, variable changes were observed in total count of leucocytes included lymphopenia and neutrophilia in G1 and G2 compared to control. In conclusion, this investigation indicated that mercury chloride has immune suppressive effects and is extremely toxic to common carp.